Unusual organization of the human T-cell receptor beta-chain gene complex is linked to recombination hotspots. - Seboun, E (1993)
Two rare Sfi I polymorphisms of 360 kb and 280 kb present within the human T-cell antigen receptor beta-chain gene complex were revealed by pulsed-field gel electrophoresis. They represent allelic variants of the polymorphic 330- and 300-kb Sfi I fragments previously described. The 360-kb polymorphism results from duplication of the 30-kb DNA fragment responsible for the 330/300-kb insertion/deletion-related polymorphism. The 280-kb polymorphism results from a 20-kb deletion from the 300-kb SfiI allele. The rare polymorphisms also map on either side of a Sal I site located near a recombination hotspot, suggesting that germline duplications and deletions arose from nonhomologous crossover events.